Biology and nature: Bionic superhydrophobic surface and principle - Ge-Zhang, Shangjie; Cai, Taoyang; Yang, Hong; Ding, Yuyang; Song, Mingbo (Frontiers in Bioengineering and Biotechnology, 2022)
Nature is the source of human design inspiration. In order to adapt to the environment better, creatures in nature have formed various morphological structures during billions of years of evolution, among which the superhydrophobic characteristics of some animal and plant surface structures have attracted wide attention. At present, the preparation methods of bionic superhydrophobic surface based on the microstructure of animal and plant body surface include vapor deposition, etching modification, sol-gel method, template method, electrostatic spinning method and electrostatic spraying method, etc., which have been used in medical care, military industry, shipping, textile and other fields. Based on nature, this paper expounds the development history of superhydrophobic principle, summarizes the structure and wettability of superhydrophobic surfaces in nature, and introduces the characteristics differences and applications of different superhydrophobic surfaces in detail. Finally, the challenge of bionic superhydrophobic surface is discussed, and the future development direction of this field is prospected.